Islamic Law and Social Change: How does Islam take a Stand? - Tolkah (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
Social change in Muslim is usually marked by the development of the Muslim civilization, social change has been absorbed through the interaction between religion and society which has implications for social processes. Social change in society always demands changes in Islamic law. Sociologically, society is always changing. Literature study research method with a qualitative approach. The conclusion from this literature research can be concluded that the relationship between Islamic law and social change is reciprocal and influences each other, Islam takes a stand to be able to keep up with the times in its own way.